Dialectical Identity of the Female Discourse of Shafak’s Black Milk, on Writing, Motherhood, and the Harem Within: Identidad dialéctica del discurso femenino de la leche negra de Shafak, sobre la escritura, la maternidad y el harén interior - ABU MADI, N. B.; AL-KHALILI, R. K. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT This paper examines Elif Shafak’s feminine discourse in her novel Black Milk, on writing, motherhood, and the harem within from a Hegelian dialectical perspective to explore the diversities and multiplicity of the self in a postmodern world. The novel primarily explores a woman’s complex identity rather than the conventional man-woman dualism that marked previous feminist ideologies. Her themes that revolve around issues of singlehood, motherhood, and diversity within the self will be discussed in the light of the Hegelian terms “being,” “nothing,” and “becoming” that are characteristics of the phases of the postmodern-postfeminist character in the novel. RESUMEN Este artículo examina el discurso femenino de Elif Shafak en su novela Black Milk, la escritura, la maternidad y el haren interior desde una perspectiva dialéctica Hegeliana para explorar las diversidades y multiplicidad del yo en un mundo posmoderno. La novela explora principalmente la identidad compleja de una mujer en lugar del dualismo convencional hombre-mujer que marcó las ideologías feministas anteriores. Sus temas que giran en torno a cuestiones de soltería, maternidad y diversidad dentro del yo serán discutidos a la luz de los términos hegelianos "ser", "nada" y "devenir" que son características de las fases del carácter posmoderno-posfeminista en la novela.